Theories of labour market segmentation A critique - Loveridge, Ray; Mok, A.L (Springer US, 1979)
The objectives of this book are: to review and develop a framework of key analytical concepts in the field of labour market segmentation; to develop and test these concepts against available data; to indicate weaknesses in the data in the light of the analysis; to offer a critique of manpower policies in some European countries in the light of the foregoing analysis; and to indicate areas of further research. The authors hope that this survey of the literature and the comments that accompany it will prove useful to policy makers and students alike. The authors woulp like to acknowledge the role of the Directorate General for Social Affairs of the European Community, Brussels, in initiating and supporting the production of this volume of criticism and discussion. We have especially appreciated the role of David White, on whose advice we came to rely in directing our critique upon the application of segmental theory to matters of labour market policy. Others whose help and advice we have relied on are John Morley, also of the European Community, Peta Small, who typed the several drafts, and our respective wives and families whose encouragement and discreet silences enabled us to get past the nth draft
Keywords: Labor Economics; Labor economics; Struktur; Arbeitsmarkttheorie; Arbeitsmarkt